(3OjhGf GdoHSJjs - (3Ydj Hf eMeO Hf GdMSjf Hf jhSa Hf eMeO Hf YHO GdYRjR GdHSJj, CHh GdaJM,J (B400 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe Ydi bGajI GdgeRI bGdhG QVjJ HOhf Mbc hGdZfi jSeh HUGMHg Edi GdYdjGA s
(3BNQgG (B:s
(3aXf QjGA HGdOehY SaMJgG heG HOehY bO eQGgG GdLhi QjG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HYOg hQbJGf HGdaGQSjI hYdjgG NGJe GdLfGH GdYGdj GdCTQajs
(3hQO CjVkG JMJ Qbe (B2182s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B685s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B42 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B772s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs